Cultural Commodification in Cultural Tourism: A Case Study of Sekartaji Wayang Beber Museum - Hery Riyanto; Mutiara Arista (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2025)
This study explores the practice of cultural commodification as a strategic approach to revitalize museum-based cultural tourism, focusing on the Wayang Beber Sekartaji Museum in Pacitan, East Java. The research investigates how cultural elements, particularly wayang beber, are transformed into tourism attractions that appeal to contemporary audiences. Drawing on an exploratory qualitative method, data were collected through field observations and in-depth interviews with the museum's founder, Indra Suroinggeno, complemented by literature reviews of relevant academic works and cultural tourism reports. The findings reveal two key forms of commodification: Wayang Beber Pancasila, which integrates national ideological values into traditional visual narratives, and Kerta Dluwang, a handmade paper medium repurposed as both artwork and merchandise. These adaptations function not only as economic assets, but also as communicative tools to reintroduce local philosophy and cultural identity to the public. Rather than diminishing authenticity, the commodification at Sekartaji Museum serves as a medium for cultural reinterpretation—balancing preservation with innovation. This study underscores that when rooted in community agency and cultural knowledge, commodification can contribute to museum sustainability, increase visitor engagement, and strengthen the socio-cultural position of traditional art forms within the tourism landscape